Determinants of perceived effectiveness in crisis management and company reputation during the COVID-19 pandemic - Diena Dwiedienawati (Taylor & Francis Group, 2021)
COVID-19 pandemic is a newness to various aspect of life, including business sector. In this high uncertainty, business still need to deliver effective crisis management in order to safeguard organization reputation. Literature state that there are three important elements in crisis management which are leader, team of crisis management, and organizational communication. What type of leader and communication are the most suitable during crises? This study aims to confirm the influence of the transformational leadership style, communication quality, and team crisis to organization reputation mediated by the effectiveness of crisis management. During crisis innovation also influences the survival of organization during crises. A new type of innovation, frugal innovation type, still has limited empirical evidence. This study also aims to see how the implementation of the frugal innovation type is influenced by the transformational leadership style and influences the effectiveness of crisis management. A descriptive quantitative study was conducted in May 2020 with 293 participants from the various organizations in Indonesia. SEM-LISREL was used for data analysis. The findings show that transformational leader, crisis management team, quality of communication and frugal innovation type positively influenced the effectiveness of crisis management which will lead to corporate reputation. The main contribution of this paper is providing the body of evidence the effectiveness of transformational leadership during crisis with high uncertainty. This study is also among the first empirical study on frugal innovation type.